Effects of Acute Intracranial Pressure Changes on Optic Nerve Head Morphology in Humans and Pig Model. (1st February 2022) - Kedar, Sachin; Tong, Junfei; Bader, John; Havens, Shane; Fan, Shan; Thorell, William; Nelson, Carl; Gu, Linxia; High, Robin; Gulati, Vikas; Ghate, Deepta
ABSTRACT: Purpose: The lamina cribrosa (LC) is a layer of fenestrated connective tissue tethered to the posterior sclera across the scleral canal in the optic nerve head (ONH). It is located at the interface of intracranial and intraocular compartments and is exposed to intraocular pressure (IOP) anteriorly and intracranial pressure (ICP) or Cerebrospinal fluid (CSF) pressure (CSFP) posteriorly. We hypothesize that the pressure difference across LC will determine LC position and meridional diameter of scleral canal (also called Bruch's membrane opening diameter; BMOD). Methods: We enrolled 19 human subjects undergoing a medically necessary lumbar puncture (LP) to lower CSFP and 6 anesthetized pigs, whose ICP was increased in 5 mm Hg increments using a lumbar catheter. We imaged ONH using optical coherence tomography and measured IOP and CSFP/ICP at baseline and after each intervention. Radial tomographic ONH scans were analyzed by two independent graders using ImageJ, an open-source software. The following ONH morphological parameters were obtained: BMOD, anterior LC depth and retinal thickness. We modeled effects of acute CSFP/ICP changes on ONH morphological parameters using ANOVA (human study) and generalized linear model (pig study). Results: For 19 human subjects, CSFP ranged from 5 to 42 mm Hg before LP and 2 to 19.4 mm Hg after LP. For the six pigs, baseline ICP ranged from 1.5 to 9 mm Hg and maximum stable ICP ranged from 18 to 40 mm Hg. Our models showed that acute CSFP/ICP changes had no significant effect on ONH morphological parameters in both humans and pigs. Conclusion: We conclude that ONH does not show measurable morphological changes in response to acute changes of CSFP/ICP. Proposed mechanisms include compensatory and opposing changes in IOP and CSFP/ICP and nonlinear or nonmonotonic effects of IOP and CSFP/ICP across LC.